Tick paralysis in spectacled flying-foxes (Pteropus conspicillatus) in North Queensland, Australia: impact of a ground-dwelling ectoparasite finding an arboreal host. - Petra G Buettner (Public Library of Science (PLoS), 2013)
When a parasite finds a new wildlife host, impacts can be significant. In the late 1980s populations of Spectacled Flying-foxes (SFF) (Pteropus conspicillatus), a species confined, in Australia, to north Queensland became infected by paralysis tick (Ixodes holocyclus), resulting in mortality. This Pteropus-tick relationship was new to Australia. Curiously, the relationship was confined to several camps on the Atherton Tableland, north Queensland. It was hypothesised that an introduced plant, wild tobacco (Solanum mauritianum), had facilitated this new host-tick interaction. This study quantifies the impact of tick paralysis on SFF and investigates the relationship with climate. Retrospective analysis was carried out on records from the Tolga Bat Hospital for 1998-2010. Juvenile mortality rates were correlated to climate data using vector auto-regression. Mortality rates due to tick paralysis ranged between 11.6 per 10,000 bats in 2003 and 102.5 in 2009; more female than male adult bats were affected. Juvenile mortality rates were negatively correlated with the total rainfall in January to March and July to September of the same year while a positive correlation of these quarterly total rainfalls existed with the total population. All tick affected camps of SFF were located in the 80% core range of S. mauritianum. This initial analysis justifies further exploration of how an exotic plant might alter the relationship between a formerly ground-dwelling parasite and an arboreal host.